Durability of Brittle Material Subjected to Static Loads - Mianowski, K. M. (Engineering Transactions, 1996)
In the paper the method of estimation the durability of brittle materials is presented. The durability of highly stressed materials is an experimental quantity, which may be determined in a laboratory. To find out the durability of less stressed materials it has been assumed that the fatigue is related to the thermal vibrations of the microstructural elements. As an example, the durability of the tendons in prestressed structures is calculated.